Wide band circularly polarised diversity antenna for satellite and mobile communication. Issue 13 (19th September 2017) - Kharche, Shilpa; Reddy, G. Shrikanth; Gupta, Rajiv Kumar; Mukherjee, Jayanta
Abstract : A wide band circularly polarised diversity antenna consisting of closely spaced monopole radiators is proposed. Two novel, microstrip fed‐printed monopoles are designed on a common ground plane. The ground plane which is asymmetric with respect to the feed line along with the planar monopole structure is used to achieve circular polarisation. The monopoles which are symmetric with respect to the vertical axis produce orthogonally polarised waves. A modified split ring resonator‐like structure is designed on the ground plane to achieve high port‐to‐port isolation. The impedance bandwidth (Voltage Standing Wave Ratio < 2) of the proposed antenna is 45.53% which covers the frequency band between 1.73 and 2.75 GHz. Isolation of >18 dB between the radiating elements is achieved. The proposed antenna provides an axial ratio (AR < 3 dB) bandwidth of 41.28% between 1.73 and 2.63 GHz. The radiation patterns are stable and the envelope correlation coefficient is <0.005 over the operating band. The proposed structure achieves efficiency >70% and gain >2 dBic over the frequency band between 1.73 and 2.63 GHz.